Resolution of Compensation for Crime Victims as the Responsibility of the State through the LPSK Institution Examined from the Perspective of Legal Certainty - Rosalina Indah Sari (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
The state, through LPSK (the Witness and Victim Protection Agency), serves as the forefront in resolving compensation issues for crime victims, as a form of responsibility and guarantee from the state to its citizens, as well as protection for crime victims. LPSK, an abbreviation for the Witness and Victim Protection Agency, is an institution tasked with providing protection and rights to witnesses and/or victims, in accordance with Law Number 13 of 2006 concerning Witness and Victim Protection. The guarantee provided by the state through LPSK is the right to equal legal certainty. This has been emphasized in Article 28D, paragraph (1) of the 1945 Constitution, which states that "Every person has the right to recognition, guarantees, protection, and fair legal certainty as well as equal treatment before the law." The resolution of compensation is regulated in Law No. 13 of 2006 jo. Law No. 31 of 2014, PERMA (Chief Justice Regulation) No. 1 of 2022, Government Regulation (PP) No. 8 of 2014, and PP No. 7 of 2018. These regulations are intended as state guarantees in protecting the rights of crime victims. Unfortunately, these regulations only cover compensation in specific cases. Additionally, the form of non-monetary compensation promised by the state through legislation is unclear in terms of the monetary value. This becomes challenging to implement due to the lack of clarity regarding the form and scope of compensation provision. The obstacles in resolving this compensation issue need to be overcome so that crime victims can obtain certainty in their compensation rights. Revision or creation of regulations related to the implementation of non-monetary compensation should be considered as the state's responsibility in compensating victims. This is based on research findings using a descriptive-analytical method in normative legal research. Based on the research results, there is a gap in the regulations described by the author regarding the explanation of non-monetary compensation in compensation payments. This causes the process to become complicated and seemingly does not provide certainty to the victims. Moreover, there is no clarity regarding the amount of compensation, although the calculation of losses has been thoroughly regulated in paragraph (1), including injured victims, deceased victims, loss of income, and/or property damage. The determination of compensation amounts is done by LPSK after obtaining approval from the minister responsible for finance. Ideally, the state through LPSK should have a standard value as a benchmark to ensure victims receive guaranteed compensation. As the compensation offered by the law is not always in the form of money, this raises concerns for victims in obtaining their compensation rights. Compensation itself is the obligation of the state through LPSK in protecting the rights of victims. Based on assessments from various journals, the author assumes that the government needs to demonstrate consistency in the payment of compensation regardless of case classification. This is intended as a form of protection for all citizens and to provide assurance of the protection of the rights of crime victims outside the classification of relevant laws on who is entitled to receive compensation. Revision or creation of regulations related to the implementation of non-monetary compensation, if not in the form of money, is necessary as the state's responsibility in compensating crime victims.